A green method for decolorization of polysaccharides from alfalfa by S-8 macroporous resin and their characterization and antioxidant activity. Issue 14 (24th March 2023) - Yu, Xiaohong; Mu, Na; Liu, Xiaochen; Shang, Yueling; Wang, Dujun; Li, Fengwei
Abstract : The decolorization process and adsorption mechanism of pigment molecules in alfalfa polysaccharides by S-8 resin were studied. Meanwhile, the physicochemical properties and antioxidant activity of alfalfa polysaccharides were analyzed. Abstract : In this study, the decolorization conditions of polysaccharides extracted from alfalfa by S-8 macroporous adsorption resin were optimized through the response surface method, and the physicochemical properties and antioxidant activity of decolorized polysaccharides were investigated. The optimal decolorization conditions were determined to be as follows: the amount of S-8 macroporous adsorption resin was 1.4 g, the adsorption time was 2 h, and the adsorption temperature was 58 °C. Under these optimal conditions, a decolorization ratio of 71.43 ± 0.23% was achieved, which was consistent with the model hypothesis. The adsorption curve showed that S-8 macroporous adsorption resin adsorption of pigment molecules in alfalfa polysaccharides (APS) agreed with the Freundlich and pseudo-second-order equations, and the adsorption was a spontaneous endothermic process. High-performance liquid chromatography (HPLC) analysis of monosaccharide composition showed that APS was composed of mannose, glucose, galactose, arabinose and glucuronic acid in a molar ratio of 1.18 : 8.04 : 1.22 : 0.92 : 1. The results of antioxidant activity studies showed that APS had strong scavenging activity against ABTS, DPPH and hydroxyl radicals. This study will help to further understand the adsorption mechanism of macroporous resin on polysaccharide pigment molecules and lay a basis for evaluating their physiological activity.